2019
DOI: 10.1093/fampra/cmz081
|View full text |Cite
|
Sign up to set email alerts
|

‘I could have made those changes years earlier’: experiences and characteristics associated with receiving a prediabetes diagnosis among individuals recently diagnosed with type 2 diabetes

Abstract: Background Prediabetes increases the risk of developing type 2 diabetes (T2D). Improving diet quality is key in preventing this progression, yet little is known about the characteristics of individuals with prediabetes or the nutrition care they receive. Objectives This study aims to identify characteristics and experiences associated with receiving a prediabetes diagnosis prior to developing T2D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…12 There were few associations between patient characteristics and the likelihood of their prediabetes being identified, suggesting non-patient factors may be more predictive of prediabetes identification and management. 12 A key non-patient related factor associated with prediabetes management may include how general practitioners (GPs) identify and manage prediabetes. When surveyed, GPs note the importance of nutrition in the chronic disease management of patients.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…12 There were few associations between patient characteristics and the likelihood of their prediabetes being identified, suggesting non-patient factors may be more predictive of prediabetes identification and management. 12 A key non-patient related factor associated with prediabetes management may include how general practitioners (GPs) identify and manage prediabetes. When surveyed, GPs note the importance of nutrition in the chronic disease management of patients.…”
Section: Discussionmentioning
confidence: 87%
“…25 Patients have previously reported receiving limited, 'vague' or inconsistent dietary advice following a prediabetes diagnosis. 12 The current study shed light on why this might be, with HCPs stating that competing priorities and limited time made it difficult to discuss diet at every appointment. Time constraints in GP visits are frequently cited as barriers to providing nutrition care.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is possible that individuals who did not make meaningful diet quality change during this period previously made changes when diagnosed with pre-diabetes. However, another analysis of the 3D study sample showed there were no differences in diet quality at baseline between those diagnosed with pre-diabetes and those who had not received a pre-diabetes diagnosis 25 . Another possibility is that some participants made changes immediately after receiving a diagnosis but before completing the baseline survey of the 3D study.…”
Section: Discussionmentioning
confidence: 95%